2019
DOI: 10.1002/ca.23333
|View full text |Cite
|
Sign up to set email alerts
|

The pecs anesthetic blockade: A correlation between magnetic resonance imaging, ultrasound imaging, reconstructed cross‐sectional anatomy and cross‐sectional histology

Abstract: The interfascial thoracic wall blockades Pecs I and Pecs II are increasingly applied in breast and axillary surgery. Despite the clear anatomical demarcations depicted at their introduction, the clinical outcome is more variable than would be expected based upon the described anatomy. In order to elucidate factors that explain this variability, we evaluated the spread of each injectionmedial Pecs I, lateral Pecs I, the deep injection of the Pecs II-separately. A correlation of in vivo landmarks and ultrasound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…). The seven cohort studies published in the peer‐reviewed literature had a median (IQR [range]) score of 7 (7–7 ) on the 9‐point Newcastle‐Ottawa Scale, whereas the six cohort studies published as abstracts or posters had a median (IQR [range]) score of 6 (5.25–6 ) (see also Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…). The seven cohort studies published in the peer‐reviewed literature had a median (IQR [range]) score of 7 (7–7 ) on the 9‐point Newcastle‐Ottawa Scale, whereas the six cohort studies published as abstracts or posters had a median (IQR [range]) score of 6 (5.25–6 ) (see also Supporting Information, Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…that a pre‐incisional single‐injection serratus anterior plane block improves early post‐thoracotomy analgesia compared with systemic analgesia alone . The serratus anterior plane block group had significantly lower pain scores up to 9 h postoperatively (median [range] scores ranging from 1 [0–3] to 3 [0–5] vs. 2 [0–5] to 4 ; IQR not reported); and lower 24‐h opioid requirements. This is supported by level 3 evidence from a retrospective study comparing postoperative deep serratus anterior plane block with systemic opioids alone in 40 patients .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LPN, which lies in the interpectoral space (Blanco, ), contributes to the innervation of both the shoulder joint capsule and the acromioclavicular joint (Wrete, ; Aszmann et al, ; Tran et al, ). The injection of anesthetic drugs into the interpectoral space, called the Pecks blockade, is a safe technique for pain control in breast surgery and some of its variants can reach the LPN with minimal involvement of other nerves (Blanco, ; Pérez et al, ; Versyck et al, ). Therefore, a triple approach (AN, SSN, and LPN) could be used when combined AN and SSN block is not enough to provide full pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…However, the description of the blocks’ performance is unclear and lacks details of level of block, probe position and orientation and needle direction, all important factors required to interpret the results. For example, a recent anatomical study of the Pecs blocks showed that the site of injection influences the effectiveness of the block as it determines the extent of spread, and consequently mass of local anaesthetic, reaching target nerves .…”
mentioning
confidence: 99%